Al-Qur’an Dalam Kajian Kontemporer - Samsul Ariyadi (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2022)
The Qur'an is a law and a way of life for friends, the food for their hearts, the decoration of their eyelids. Thus, its influence is very visible in their education and direction of life. They are a generation of pioneers and role models to emulate. Indeed, the companions of the Prophet were the first generation to feel when the Qur'an came down to the Prophet Muhammad. The Prophet received the Qur'an from Gabriel and also directly from Allah. Then he conveyed to his friends when he came down without lacking or forgetting a single letter. The Companions heard the Qur'an from the Prophet as if he had come down directly to them. The verses of the Qur'an inspire reason and remind people to do good deeds, and also call to think about the creation of creatures. The companions heard these verses. If their life is not in accordance with the Qur'an, they immediately change their lifestyle with safe guidelines, according to what they understand from the Qur'an.